Risk classification model in rural T-form intersections and time to evasion evaluation as surrogate safety measure - Torres Flores, Alejandro; Torres Avilés, Francisco; Pardillo Mayora, José Mª (Revista Ingeniería de Construcción, 2010)
In the intersections, the drivers confront many options related to the way, speed and trajectory, which ones in combination to many options of traffic movements, they make difficult the task of the conductor and considerably increase the potential occurrence of an accident. In this paper, data of traffic conflicts are used, taken in rural T-form intersections from Talagante district in the Metropolitana region, Chile. Using the principal component analysis, an index are proposed that represents the risk level of each traffic conflict in an intersection, determining that the highest values of the index are related to a greater risk of than a traffic conflict it finished in accident, whereas low values indicate a smaller risk. After that, a model of classification of the risk in intersections is developed, applying the theory of decision trees. Finally, Time to Evasion is validated like quantifying variable of the traffic conflicts, taking as it bases studied variables at world-wide level, like Time to Collision and Post – encroachment Time.